2022
DOI: 10.1002/clt2.12096
|View full text |Cite
|
Sign up to set email alerts
|

Natural pollen exposure increases in a dose‐dependent way Fraction of exhaled Nitric Oxide (FeNO) levels in patients sensitized to one or more pollen species

Abstract: Background Co‐exposures and polysensitization to several pollen species are very common in real life practice. However, little information exists on allergic symptoms and airway inflammation related to natural pollen exposure in large general population samples. Objective To assess the combined effect of sensitization and/or exposure to one or more pollen species on Fraction of exhaled Nitric Oxide (FeNO) levels. Methods Within Gene Environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Likewise, a study of adults in Italy (N = 1070) found that airway inflammation was related in an exposure-dependent, interactive manner to both sensitization and the number of tree, grass, and weed pollen species present in the ambient environment. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a study of adults in Italy (N = 1070) found that airway inflammation was related in an exposure-dependent, interactive manner to both sensitization and the number of tree, grass, and weed pollen species present in the ambient environment. 21 …”
Section: Discussionmentioning
confidence: 99%